Evaluation of pre-harvest interval for pesticides on different vegetables in Bangladesh: Pre-harvest interval for pesticides (Journal of the Bangladesh Agricultural University, 2018)
A study was conducted to evaluate the pre-harvest interval (PHI) for pesticides on different vegetables in Bangladesh. Data were collected from selected 330 vegetable farmers of eleven districts- Bogra, Joypurhut, Rangpur, Gaibandha, Jessore, Jhenaidah, Magura, Khulna, Satkhira, Kustia and Chuadangha in 2013. The interview schedule containing direct questions with appropriate scales were prepared according to the objectives of the study and data were collected from the vegetable farmers. The recommendation rate of the pesticides was used in the vegetables field of the study area. The highest and the lowest amount of highly toxic vegetables were harvested by the farmer of Jhenaidah and Gaibandha districts, having an average mean values of 40 and 10%, respectively. The result also demonstrated that the brinjal was the vegetables whose PHI was the lowest receiving highest toxic vegetable among all vegetables under consideration in this study. The green banana and green papaya proved to be non toxic vegetables among all vegetables. Fifty percent farmer followed the PHI 0-2 days of pesticide for brinjal those are highly toxic. No farmer used pesticide before at least one month of harvesting in case of green banana and green papaya. Though the lowest amount of highly toxic vegetables were harvested by the farmer of Gaibandha district, the overall vegetables those were harvested by the farmer of Satkhira district that was comparatively less toxic than the other districts. The farmers of this district harvested 20% non toxic and 13.33% slightly toxic vegetables. This study provides information on the knowledge, attitudes, and practices of vegetable farmers in the eleven districts of Bangladesh regarding pesticide use. Survey responses indicate the widespread improper use of pesticide especially inadequate PHI that pose hazards to the human health and environment.J. Bangladesh Agril. Univ. 16(3): 444–447, December 2018